2022
DOI: 10.1002/cpe.7180
|View full text |Cite
|
Sign up to set email alerts
|

AMD‐CNN: Android malware detection via feature graph and convolutional neural networks

Abstract: Summary Android malware has become a serious threat to mobile device users, and effective detection and defence architectures are needed to solve this problem. Recently, machine learning techniques have been widely used to deal with Android malicious apps. These methods are based on a simple feature set and have difficulty detecting up‐to‐date malware. Therefore, more robust and efficient classification methodologies are needed. In this article, AMD‐CNN, an Android malware detection tool, is proposed, and it u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 69 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Table 10 shows the performance comparisons with related and recently published research. Arslan et al [15] proposed to create a graphical Android malware detection tool. The features of Androidmanifest.xml are extracted and converted to a one-or-zero vector.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10 shows the performance comparisons with related and recently published research. Arslan et al [15] proposed to create a graphical Android malware detection tool. The features of Androidmanifest.xml are extracted and converted to a one-or-zero vector.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…It has previously been demonstrated that CFG-based analysis can be combined with machine learning techniques to produce strong malware classification tools [4]. Arslan et al [15] suggested developing a graphical Android malware detection tool. A one-or-zero vector is extracted from the features of Androidmanifest.xml.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In graph-based Android application detection, Marwan Omar [ 30 ] used his own graph convolutional neural network as a baseline, combined with expert data science methods, and finally achieved 99.183% accuracy in Android malware detection by continuously fine-tuning the model. RecepSinan Arslan [ 31 ] also uses a graph convolutional neural network, but the novelty is that it converts the data obtained in AndroidManifest.xml into image data and sends it to the neural network for learning, and its final accuracy rate reaches 96.2%. Shanxi Li [ 32 ] et al first extracted API call sequences from malware code and generated directed cyclic graphs, then used Markov chain and principal component analysis methods to extract feature maps of the graphs and designed a classifier based on graph convolutional networks, and finally achieved 98.32% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%